PERAN GEOMORFOLOGI DALAM ANALISIS RISIKO BENCANA LONGSOR DI DAERAH KARANGGAYAM, KABUPATEN KEBUMEN, PROVINSI JAWA TENGAH, INDONESIA - Retongga, Nofrohu; Putri Wijaya, Nurhikmah; Anwar, Ardian; Akbar, Rizky; Ramadhan, Ilfan Prabu; Anjani, Dito Fatria; Darmawan, Wawan; M. Haris; Firdaus; Munandar, Agus; Kurniawan, Wawan (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2024)
The aim of this study was to determine the role of geomorphology in analyzing the risk of landslides disasters in a complete and comprehensive manner in the Karanggayam area, Kebumen Regency, Central Java Province, based on threat, vulnerability, resilience, and exposure factors. This research is descriptive in nature, so the data source relies on the results of field observations, which are then supported by data from laboratory analysis. The stages in this research were divided into data acquisition, data analysis, and studio stages. Studies of drainage patterns and geomorphological studies can be used as indicators to analyze the risk of landslides, such as landforms, soil thickness, slope, lithology, land use, and vegetation, as well as other indicators such as population density and rainfall, while indicators of resilience factors and exposure factors such as early warning systems, evacuation routes, health facilities, the economy, road borders, and river borders are part of social, economic, and public health. The risk of landslides in the Karanggayam area has three levels: low, medium, and high.